Physiotherapy for plantar fasciitis: a UK-wide survey of current practice. Issue 2 (June 2017) - Grieve, Rob; Palmer, Shea
Abstract: Objectives: To identify how United Kingdom (UK) physiotherapists currently diagnose, assess and manage plantar fasciitis in routine practice. Design: Online questionnaire survey. Participants: Practising physiotherapists across the UK who treat patients with plantar fasciitis. Methods: Physiotherapists were approached via 'interactive Chartered Society of Physiotherapy (CSP)' online networks and an email database of clinical educators in South West England. An online questionnaire was developed by reviewing similar existing physiotherapy surveys and consultation with experienced musculoskeletal researchers/clinicians. Descriptive statistics were used to analyse the data. Results: 285 physiotherapists responded, with 257 complete survey responses. Pain on palpation and early morning pain were the most common diagnostic criteria, with some physiotherapists using no formal test criteria. Advice (237/257, 92%), plantar fasciitis pathology education (207/257, 81%) and general stretching exercises (189/257, 74%) were most routinely used. Prefabricated orthotics, custom made orthotics and night splints were seldom always used. For the manual therapy approach, the most frequently used modalities were massage, myofascial release, specific soft tissue mobilisations and myofascial trigger point therapy. Commonly used outcome measures were pain assessment, functional tests and range of movement. Conclusions: Physiotherapists appeared to follow most of the established diagnostic criteria for PF, but have not followed established outcome measure guidelines. Advice as well as education with an emphasis on self-management including calf/hamstring stretching was the most commonly reported treatment approach. There was uncertainty whether this approach accurately reflected clinical practice used throughout the UK, owing to potential response bias/unknown response rate and the low number of patients with PF treated by the respondents.